P116 A systematic review to identify and collate the patient-centred factors influencing patient journeys through clinical trials. (11th November 2022) - Dobra, RA; Boeri, M; Elborn, JS; Kee, F; Madge, S; Matthews, J; Wilson, G; Davies, JC
Abstract : Background: Patient-centred trial design and delivery; improves recruitment and retention, with a direct impact on increased cost and time efficiency of research; increases participant satisfaction; encourages participation by a more representative patient group; allows research teams to better meet participants' psychosocial needs; and ensures outcomes that matter to patients are prioritised. Research in this area is increasing, however most explorations focus on narrow facets of trial participation. The aim of this project was to systematically identify the breadth and diversity of patient-centred factors influencing participation and engagement in clinical trials and collate these into an organising framework. Methods: Robust qualitative and mixed methods systematic reviews are becoming increasingly common in health research. The protocol for this review was prospectively registered on PROSPERO, CRD42020184886. We used the SPIDER (Sample, Phenomenon of Interest, Design, Evaluation, Research type) framework as a standardised systematic search strategy tool. 3 databases were searched as well as references checking, and thematic synthesis was conducted. Screening agreement was performed (Cohen's kappa coefficient 0.97, excellent agreement) and code and theme checking were conducted by 2 independent researchers. Results: Data were drawn from 285 peer-reviewed articles. Approximately half were in oncology, with the others in 22 different specialities. 7 (2.5%) were in respiratory medicine. 300 discrete factors were identified, which were sorted into 13 major themes and subthemes. Themes and level-one subthemes are shown in the table 1 . Many of the identified factors are straightforward, generalisable and transferable across most specialities and disease models. Others are complex, at times contradictory, and may be context or disease specific. Conclusions: We have used a robust systematic review methodology to develop a framework to guide other researchers towards the important patient-centred themes to consider when designing and delivering trials. Some of the identified factors are disease specific. Respiratory medicine currently lags behind other specialities such as oncology in identifying factors influencing patient perceptions and experiences of trials. Given the benefits of understanding and incorporating patient views into research, and the volume of active respiratory research, we suggest more exploration is needed in respiratory medicine and its subspecialities.